Large deviation probabilities for UH-statistics - Borovskikh, Yu. V. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
ForU-statistics taking values in a Hilbert space, we obtain estimates of the rate of convergence in the central limit theorem.